PERANCANGAN TOPOLOGI LAN PADA PERCETAKAN DARRA MENGGUNAKAN APLIKASI SISCO PACKET TRACER - Prayogi, M. Bagus; Setia Dewi, Mita; anshori (Program Studi Informatika, 2024)
As globalization progresses, technological developments are increasingly advanced, and human resource skills are needed in various fields. Computer network technology is proliferating because of the community's need for services using computer networks. This research was conducted to design a computer network using Cisco router switches at the Dara printing house, the owner of this printing house Aris Munandar, is located in BK4, kumpul Rejo Village, East Buay Madan District, East Ok, South Sumatra. This printing network has not been typologized LAN and only uses wireless via Wi-Fi. Another problem is that it only has 3 computers and 1 laptop, but only 1 computer and 1 laptop are connected to WiFi. The type of network designed refers to a local area network (LAN). The purpose of this network design is to design a LAN typology that facilitates data transfer and connectivity of multiple computers within a single local area. In addition, LAN networks can also improve employee efficiency and performance. This research was conducted using qualitative methods using direct observation in the field. The network development method used in this study is the NDLC (Network Development Life Cycle) method which consists of the stages of analysis, design, prototyping simulation, and management. After being developed through several stages, the results of this research were developed using Cisco Packet Tracer to analyze and design network designs.